(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
A story is told of a tourist who visited an unnamed African country and was infected by a jigger. On his return to his home country he noticed a swelling in the big toe accompanied by intense itch. He consulted his family doctor who in turn referred him to a consultant. The consultant was baffled and referred the patient to a specialist on tropical medicine. Neither the family doctor, the consultant nor the specialist had ever seen a jigger. The specialist diagnosed it as a fast growing tumor and recommended amputation of the toe. However before he was admitted to hospital the distraught jigger host narrated his ordeal to an African student in the neighbourhood. The student instantly recognized the "tumor" as a jigger and unceremoniously removed it with a safety pin.